2023
DOI: 10.3390/ijms24043227
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cell Implants for the Treatment of Focal Chondral Defects of the Knee in Animal Models: A Systematic Review and Meta-Analysis

Abstract: Osteoarthritis remains an unfortunate long-term consequence of focal cartilage defects of the knee. Associated with functional loss and pain, it has necessitated the exploration of new therapies to regenerate cartilage before significant deterioration and subsequent joint replacement take place. Recent studies have investigated a multitude of mesenchymal stem cell (MSC) sources and polymer scaffold compositions. It is uncertain how different combinations affect the extent of integration of native and implant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The selection of seed cells is of great significance for tracheal cartilage repair [ 58 ]. BMSCs, a commonly used cell type with definite chondrogenic capacity, were employed as seeding cells [ 59 ]. BMSCs can express various surface antigens, such as CD71, CD44, CD105, CD90 and SH2, SH3, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of seed cells is of great significance for tracheal cartilage repair [ 58 ]. BMSCs, a commonly used cell type with definite chondrogenic capacity, were employed as seeding cells [ 59 ]. BMSCs can express various surface antigens, such as CD71, CD44, CD105, CD90 and SH2, SH3, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to date, the pathogenesis of RA and the development of effective early diagnosis and treatment modalities remain largely unresolved, resulting in profound disability and premature mortality . Numerous studies have showcased the burgeoning interest in stem cell-based therapy for augmenting osseointegration efficiency in the RA, and BMSCs can alleviate the symptoms of RA, encompassing the inhibition of local inflammatory cytokines and enhancement of cartilage healing. , Our previous study demonstrated, for the first time, that IL-1β siRNA-BMSCs are more effective in repairing cartilage defects associated with RA than BMSCs alone. This finding suggests that IL-1β siRNA-BMSCs may represent a novel and promising strategy for the treatment of RA .…”
Section: Introductionmentioning
confidence: 99%
“… 10 Cartilage tissue engineering assumes the construction of scaffold materials suitable for defect sites, the isolation of specific tissues or cells from the body, in vitro expansion and culturing, the inoculation of the expanded cells into a specific scaffold, and the reimplantation of the cartilage component carrying the seed cells into a defect site. 11 However, direct implantation of tissue-engineered scaffolds for articular cartilage repair can hardly achieve good results.…”
Section: Introductionmentioning
confidence: 99%